Impact and implementation of a sustainable regional telestroke network. Issue 11 (5th November 2017) - Ranta, Annemarei; Lanford, Jeremy; Busch, Suzanne; Providence, Carolyn; Iniesta, Ivan; Rosemergy, Ian; Wilson, Andrew; Cariga, Pietro; Richmond, Victoria; Gommans, John
Abstract: Background: Telestroke uses videoconferencing technology to allow off‐site experts to provide stroke thrombolysis decision support to less experienced front line clinicians. Aim: To assess the impact of a new telestroke service on thrombolysis rates and door‐to‐needle times in participating provincial hospitals and service resources to aid transition to a sustainable telestroke service. Methods: This is a sequential comparison of 'pre' (December 2015 to May 2016) and 'post' (June 2016 to December 2016) implementation outcomes. The main outcomes were thrombolysis rate and door‐to‐needle time. All patient data were captured prospectively in a central database. Data captured and analysed also included technical problems, consumer and clinician feedback, and additional service resources required. Results: Over the study period, 164 telestroke assessments were completed, including the 'hub' hospital. Among the participating provincial hospitals, 21 of 343 patients (6.1%) were thrombolysed in the 6‐months prior to June 2016 and 50 of 318 patients (15.7%) during the 6‐month following implementation of telestroke; odds ratio 2.86 (95% confidence interval 1.68–4.89); P = 0.0001. Overall, mean (standard deviation) regional hospital door‐to‐needle time reduced from 79.6 (31.4) to 62.7 (23.3) min ( P = 0.015). Videoconferencing failure occurred in 4.8% of cases. Consumer and clinician feedback was positive. The main resource challenge was doubling of out‐of‐hours neurologist workload. Conclusion: Telestroke was associated with a significant increase in thrombolysis rate and reduction in door‐to‐needle time in provincial hospitals indicating improved patient care. Quantification of the extra neurologist workload allowed for a seamless transition to 'business as usual' using a novel annual subscription funding and service model.